1971
DOI: 10.1161/01.cir.44.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Combined Papillary Muscle and Left Ventricular Wall Dysfunction as a Cause of Mitral Regurgitation

Abstract: Papillary muscle infarction was produced in 16 mongrel dogs by placing sutures around the base of one of the papillary muscles. In addition, patchy infarction of the adjacent left ventricular wall was produced by placing an Ameroid constrictor around the appropriate coronary artery. Mitral insufficiency developed in 14 of these animals; it was severe in four and mild to moderate in ten. Mitral insufficiency was not produced by isolated infarction of a papillary muscle or by isolated infarction of the left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
6

Year Published

1976
1976
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(38 citation statements)
references
References 13 publications
2
30
0
6
Order By: Relevance
“…Experimental damage to the PMs themselves, however, fails to produce MR acutely without damage to the underlying myocardial wall as well. 16 Burch et al 14,15 alternatively postulated restricted leaflet motion. The PMs, normally parallel to the LV long axis and perpendicular to the leaflets, efficiently balance forces generated by ventricular pressure on the leaflet surface.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental damage to the PMs themselves, however, fails to produce MR acutely without damage to the underlying myocardial wall as well. 16 Burch et al 14,15 alternatively postulated restricted leaflet motion. The PMs, normally parallel to the LV long axis and perpendicular to the leaflets, efficiently balance forces generated by ventricular pressure on the leaflet surface.…”
Section: Mechanismsmentioning
confidence: 99%
“…First, although PM damage does not produce MR acutely, MR does occur in the chronic phase of ethanol injection, with PM scarring and retraction. 16 Second, occasional patients with MI actually do have prolapse with PM elongation. 38 These observations, rather than disproving tethering, actually confirm that tethering distance is the final common pathway determining the level of leaflet coaptation.…”
Section: Mechanismsmentioning
confidence: 99%
“…6). However, multiple experimental studies have reported that isolated PM dysfunction did not cause ischemic MR. [36][37][38][39][40] In addition, clinical studies have also reported that leaflet prolapse in patients with ischemic MR is very rare. 6)7)20) Therefore, the relationship between PM dysfunction and ischemic MR is not yet clear.…”
Section: P Pm M D Dy Ys Sf Fu Un Nc Ct Ti Io On Nmentioning
confidence: 99%
“…Investigative work done by Underwood et al (1970) and Mittall et al (1971) in dogs has shown that experimentally induced ischemia in papillary muscles does not commonly lead to mitral regurgitation unless there is involvement of the adjoining free ventricular wall. The degree of ischemic compromise of the remaining left ventricle is an additional major factor in determining the magnitude of the regurgitation.…”
Section: Clinical Presentationmentioning
confidence: 99%